2013
DOI: 10.1016/j.celrep.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors Mediate the Enzymatic Disassembly of Promoter-Bound 7SK snRNP to Locally Recruit P-TEFb for Transcription Elongation

Abstract: SUMMARY The transition from transcription initiation into elongation is controlled by transcription factors, which recruit P-TEFb to promoters to phosphorylate RNA polymerase II. A fraction of P-TEFb is recruited as part of the inhibitory 7SK small nuclear ribonucleoprotein (snRNP), which inactivates the kinase and prevents elongation. It is unclear, however, how P-TEFb is captured from the promoter-bound 7SK snRNP to activate elongation. Here, we describe a novel mechanism by which transcription factors media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
142
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(152 citation statements)
references
References 49 publications
5
142
1
Order By: Relevance
“…Mass spectrometry analysis of this fraction (Fig. 1A) revealed the presence of several proteins known to be required for Tat activity, including CycT1, AFF4, Cold Spring Harbor Laboratory Press on May 9, 2018 -Published by genesdev.cshlp.org Downloaded from and SirT1, and a CDK9 T-loop phosphatase, PPM1G (McNamara et al 2013). Consistent with previous reports (Sobhian et al 2010), the Tat fractions also contained inhibitory 7SK snRNP subunits MECPE and LARP7 and not HEXIM1.…”
Section: Hiv-1 Tat Interacts Directly With the Ssu72 Rnapii Ctd Phospsupporting
confidence: 75%
“…Mass spectrometry analysis of this fraction (Fig. 1A) revealed the presence of several proteins known to be required for Tat activity, including CycT1, AFF4, Cold Spring Harbor Laboratory Press on May 9, 2018 -Published by genesdev.cshlp.org Downloaded from and SirT1, and a CDK9 T-loop phosphatase, PPM1G (McNamara et al 2013). Consistent with previous reports (Sobhian et al 2010), the Tat fractions also contained inhibitory 7SK snRNP subunits MECPE and LARP7 and not HEXIM1.…”
Section: Hiv-1 Tat Interacts Directly With the Ssu72 Rnapii Ctd Phospsupporting
confidence: 75%
“…HEXIM1 can be recruited to promoter and 5Ј proximal regions in genes directly or via RNA-binding proteins such as SC35, presumably for loading of P-TEFb (52,53). Although chromatin immunoprecipitations revealed HEXIM1 and LaRP7 on DNA, they did not demonstrate the presence of 7SK or the entire 7SK snRNP.…”
Section: Discussionmentioning
confidence: 95%
“…15,16 However, components of the 7SK snRNP have been cross-linked to the HIV promoter and it has been suggested that the extraction of P-TEFb occurs at the promoter. 42,43 Because Tat has low affinity to TAR in the absence of P-TEFb, 13 whether the extraction takes place in the nucleoplasm or in close proximity to the HIV promoter is not clear. The order of assembly of the Tat•AFF4•P-TEFb complex is also not resolved.…”
Section: Discussionmentioning
confidence: 99%